ANALISIS PENGARUH KEKUATAN PASAR DAN STRUKTUR EFISIENSI TERHADAP RETURN ON ASSET (ROA) BANK - CAHYA I, NOVIA (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract: This studyaims to analyze the effect of Market Power (MP) and the Efficiency Structure (ES) on ROA of banking companies that listedon the Indonesia Stock Exchange in 2011-2012. The population of this study were 38 commercial banks and the total of sample are 24 banks with purposive sampling technique. The analysis technique used in this study is multiple linear regression analysis. Based on the results of F test is known that there is a significant effect of the variable market concentration, market share, BOPO and NIM simultaneouson ROA bank. The results also showed that 95.8 % ROA is affected by variable market concentration, market share, BOPO and NIM while the remaining 4.2 % is explained by other variables. Based on the t test can be seen that there is a significant effect of the variable BOPO and NIM on ROA. As for market concentration and market share has no significant effect on ROA. Keywords:market concentration, market share, BOPO, NIM and ROA.